Role of workplace handling parameters in the material handling equipment selection - Telek, Péter (Journal of Production Engineering, 2023)
Usually, the handling characterisation of workplaces is not taken into consideration during the handling equipment selection process, so the handling solutions are not optimized and require additional modifications. If we could exactly define the handling parameters of workplaces and take them into account before the selection of the handling equipment, the result will be better suit. In this paper, the handling parameters of production workplaces and their effects to the handling solutions are presented. The focus is on the external handling process and the relation among workplace and handling equipment parameters, and an example is also presented.